Structure, Function and Insertion of the Human Vocal Folds - Paulsen, Friedrich; Tillmann, Bernhard (Advances in Oto-Rhino-Laryngology, 2020)
We here summarize the structures of the laryngeal vocal fold as well as its insertion structures at the anterior commissure and at the area of the vocal process and place these findings within the context of biomechanical, functional, and clinical implications.
CRIS-Team Scopus Importer:2020-11-20